Project and program risk management : a guide to managing project risks and opportunities - Wideman, R. Max (PMBOK handbook series ;, 1992)
"This handbook deals with the function of risk management in the context of program or program management. It establishes the need for examining risks or opportunities in project work and describes approaches which can lead to significant reducation of the risk as well as to better project performance." -- Forward.